2014
DOI: 10.1007/s00773-014-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Parametric bulbous bow design using the cubic Bezier curve and curve-plane intersection method for the minimization of ship resistance in CFD

Abstract: Parametric geometric modeling plays an important role in ship's hull form optimization by use of computational fluid dynamic (CFD) analysis. However, it is difficult to create satisfactory parametric modeling for some curved shapes, such as a ship's bulbous bow. In this study, the cubic Bezier curve and curve-plane intersection methods are applied to generate the parametric design of a bulbous bow in a solid modeling procedure by taking into account the input of 4 (four) design parameters. For this, a suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…The vessel under study in this paper is a US Navy Combatant DTMB, shown in Figure 3, with characteristics of the ship are given in table 1. The main reason for using this hull is that the hull geometry is a public domain [9], and extensive database of seakeeping test exists at different Froude numbers and sea state, that were carried out by Ship Design and Research Centre CTO S.A. fig. 4.…”
Section: A Reference Vesselmentioning
confidence: 99%
“…The vessel under study in this paper is a US Navy Combatant DTMB, shown in Figure 3, with characteristics of the ship are given in table 1. The main reason for using this hull is that the hull geometry is a public domain [9], and extensive database of seakeeping test exists at different Froude numbers and sea state, that were carried out by Ship Design and Research Centre CTO S.A. fig. 4.…”
Section: A Reference Vesselmentioning
confidence: 99%
“…Julio Garcia et al using finite element method based on the finite calculus for analysis of free surface flow problems [9]. A bulbous bow that has been adopted widely in a monohull should only be fitted if it will reduce the ship resistance which its effect will increase the ship speed or reduce the fuel consumption [10]. Therefore, the main objective of this research is to MATEC Web of Conferences 159, 02057 (2018) https://doi.org/10.1051/matecconf/201815902057 IJCAET & ISAMPE 2017 develop catamaran ship resistance using a bulbous bow.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the control points of the cubic B spline to generate the parametric of ship hull design as well as the parametric of bulbous bow design has been introduced with successful results [1,2,3,4]. Deddy, C [5,6] has developed the parametric bulbous bow design and submarine design are constructed using the cubic Bezier curve method and the curve-plane intersection method. The methods can be used to generate a parametric bulbous bow shape automatically using solid modeling for the optimization calculation in the effort to minimize the ship's resistance.…”
Section: Introductionmentioning
confidence: 99%